Quality Evaluation of Environmental Accounting Information Disclosure of Y Nonferrous Metal Company Based on AHP-FCE Model - Yan Li (Discrete Dynamics in Nature and Society)
Environmental accounting information disclosure is an important way to achieve the goal of “carbon peak carbon neutrality”, which plays a role in the link between economic development and environmental protection. Select Y Non-Ferrous Metal Company for case analysis, use the AHP-FCE model for comprehensive evaluation of environmental accounting information quality of the company, which use analytic hierarchy process to determine the evaluation factors and factors of weight value, and then use fuzzy synthesis method for multi-level fuzzy comprehensive evaluation. The results show that as a state-owned enterprise, the quality level of Y company’s environmental accounting information disclosure is in the “general” level in the past 5 years, and the intensity of government environmental regulation will promote the quality of the company’s environmental accounting information disclosure. Non-ferrous metal companies should enhance the concept of environmental protection, strengthen the awareness of environmental accounting information disclosure, promote technological innovation in energy conservation and emission reduction, and reduce carbon emission intensity. The government should also provide a favorable social environment and policy support for the non-ferrous metal industry to implement environmental accounting information disclosure, formulate relevant laws and regulations, and continuously strengthen supervision.